Distribution and moment characteristics of a quotient of heavy-tailed random variables - Gadeikis, Kęstutis (Lietuvos matematikos rinkinys, 2023)
Let us deal with positive i.i.d. random variables X1, . . ., Xm having a tail index α. Calculating a quotient of two biggest members in the set, we obtain a new random variable and investigate its distribution and moment properties. The method itself was proposed by prof. V. Paulauskas and co-authors in [1] and [2].
Keywords: tail index; heavy tail; Pareto